IN VITRO ANTIANGIOGENESIS ACTIVITY OF STANDARDIZED EXTRACTS OF Piper sarmentosum Roxb - Hussain, Khalid; Ismail, Zhari; Sadikun, Amirin; Ibrahim, Pazilah; Malik, Amin (Jurnal Riset Kimia, 2008)
ABSTRACT This study was undertaken to investigate the antiangiogenesis activity of standardized extracts/fractions of the leaf of Piper sarmentosum, using rat aorta model. The pulverized leaf was extracted sequentially and methanol extract was further fractionated with hexane, chloroform and ethylacetate. Both extracts and fractions were standardized by reverse phase HPLC with UV detection at 260 nm, using two markers, sarmentine and sarmentosine. Chloroform and methanol extracts have exhibited antiangiogenesis activity of 100% and 20% respectively. Antiangiogenesis activity of hexane and chloroform fractions was found to be 10% and 90% respectively, while ethylacetate fraction was found to be inactive. The analysis of most active extract and fraction has exhibited different profile by HPLC on the basis of amides. This study indicates that chloroform extract and fraction have promising antiangiogenesis activity and have potential for diseases involving angiogenesis. Keywords : antiangiogenesis activity, Piper sarmentosum Roxb.